2006
DOI: 10.1093/bja/aei265
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent dose of ephedrine and phenylephrine in the prevention of post-spinal hypotension in Caesarean section

Abstract: This study demonstrates a potency ratio of 81.2 (95% CI 73.0-89.7) for equivalence between phenylephrine and ephedrine in prevention of hypotension after spinal anaesthesia for Caesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
3
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 27 publications
0
108
3
6
Order By: Relevance
“…Based on our clinical experience, we chose doses that we considered to be approximately equipotent. However, subsequent to the commencement of our study, Saravanan et al [17] published data from which they estimated that the potency ratio of phenylephrine:ephedrine was approximately 80 : 1 (phenylephrine 100 lg = ephedrine 8 mg) when the drugs were given by infusion. Although this suggests that the doses in our study might not have been be exactly equipotent, nonetheless the doses we used fall within what we consider a normal clinical range and we do not consider that the exact choice of dose would have had an important influence on the study results.…”
Section: Discussionmentioning
confidence: 88%
“…Based on our clinical experience, we chose doses that we considered to be approximately equipotent. However, subsequent to the commencement of our study, Saravanan et al [17] published data from which they estimated that the potency ratio of phenylephrine:ephedrine was approximately 80 : 1 (phenylephrine 100 lg = ephedrine 8 mg) when the drugs were given by infusion. Although this suggests that the doses in our study might not have been be exactly equipotent, nonetheless the doses we used fall within what we consider a normal clinical range and we do not consider that the exact choice of dose would have had an important influence on the study results.…”
Section: Discussionmentioning
confidence: 88%
“…Spinal anesthesia is known as a standard technique for elective C-section due to its cost effectiveness and less amount of surgical hemorrhage [16,17]. However, the incidence of…”
Section: Discussionmentioning
confidence: 99%
“…NganKee and colleagues [12] demonstrated that in patients receiving spinal anaesthesia for Caesarean section, a prophylactic infusion of phenylephrine 100 μg/min given immediately after initiation of spinal block decreased the incidence, frequency and magnitude of hypotension compared with a control group receiving intravenous bolus of 100 μg phenylephrine given as treatment for episodes of hypotension. The lower dose of phenylephrine used in this study was to ensure a relative potency of 80:1 based on the study by Saravanet al [13].…”
Section: Discussionmentioning
confidence: 99%